Biological Magnetic Resonance Data Bank. Issue Volume 51:Issue D1(2023) (7th December 2022) - Hoch, Jeffrey C; Baskaran, Kumaran; Burr, Harrison; Chin, John; Eghbalnia, Hamid R; Fujiwara, Toshimichi; Gryk, Michael R; Iwata, Takeshi; Kojima, Chojiro; Kurisu, Genji; Maziuk, Dmitri; Miyanoiri, Yohei; et al.
Abstract: The Biological Magnetic Resonance Data Bank (BMRB, https://bmrb.io ) is the international open data repository for biomolecular nuclear magnetic resonance (NMR) data. Comprised of both empirical and derived data, BMRB has applications in the study of biomacromolecular structure and dynamics, biomolecular interactions, drug discovery, intrinsically disordered proteins, natural products, biomarkers, and metabolomics. Advances including GHz-class NMR instruments, national and trans-national NMR cyberinfrastructure, hybrid structural biology methods and machine learning are driving increases in the amount, type, and applications of NMR data in the biosciences. BMRB is a Core Archive and member of the World-wide Protein Data Bank (wwPDB).